Pengembalian fungsi pengunyahan pada anak dengan kelainan cerebral palsy dan mild mental retardation - Muh. Harun Achmad (Journal of Dentomaxillofacial Science, 2008)
Cerebral palsy is the condition marked by paralysis, weakness, inability coordinationor other deviation of motoric function, especially muscles. While mental retardation isdevelopment disturbance especially in functions and the intellectual capacity. Fromthe dentistry point of view, the paient had many disturbances because the decreasingof the capacity, include maintenance of the oral dental health. In fact, therequirements in oral and dental health care were not different from other patients, butthe implementation usually difficult. Dental care was influenced by several points,psychology, physical, and emotion. The aim of this case study is to reportconsiderations in caring inpatient, improving the chewing function and esthetics andincreased patient’s self confidence. This case represents a 17 years old man with thecerebral palsy and mild mental retardation, came to the Teeth and Mouth Clinic ofYPAC Jakarta to make denture. He complained his chewing abilitiy, and appearancebecause disturbanced and decreased his self-confidence. In this case, the patient wasmade frame denture to the teeth 41 to 45, because the ridge had been lost as a result oflosing teeth many years ago.after the therapy, it can be concluded that the difficulty inhandling the special need children patient could be overcome if the dentist studied thecharacteristics of the manifestation of his physical and psychological situation of thepublic well. Professionally a dentist could determine the attitude before planning anoperational action on a sufferer.